2013
DOI: 10.1097/md.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Therapy and the Risk of Infection in Patients With Newly Diagnosed Autoimmune Disease

Abstract: Glucocorticoid (GC) therapy is associated with the risk of life-threatening adverse events in patients with autoimmune disease. To determine accurately the incidence and predictors of GC-related adverse events during initial GC treatment, we conducted a cohort study. Patients with autoimmune disease who were initially treated with GCs in Japan National Hospital Organization (NHO) hospitals were enrolled. Cox proportional hazard regression was used to determine the independent risks for GC-related serious adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Our finding that the likelihood of developing certain GC-related AE (including myopathy, glaucoma, nausea/ vomiting, fatty liver, tuberculosis, fungal infection, and cardiovascular disease) was associated with high-dose GC therapy is also consistent with previous studies 8,26 . Our study showed that the risk of bacterial infection increased with the GC daily dose 28,29,30 . In addition, our findings supported previous results that opportunistic infections 7,23,31 such as tuberculosis and fungal infections were associated with GC use in a dose-response relationship 32 .…”
Section: Discussionmentioning
confidence: 56%
“…Our finding that the likelihood of developing certain GC-related AE (including myopathy, glaucoma, nausea/ vomiting, fatty liver, tuberculosis, fungal infection, and cardiovascular disease) was associated with high-dose GC therapy is also consistent with previous studies 8,26 . Our study showed that the risk of bacterial infection increased with the GC daily dose 28,29,30 . In addition, our findings supported previous results that opportunistic infections 7,23,31 such as tuberculosis and fungal infections were associated with GC use in a dose-response relationship 32 .…”
Section: Discussionmentioning
confidence: 56%
“…An increased risk of both pyogenic and opportunistic infection has been observed in several immune-mediated disorders such as rheumatoid arthritis, system lupus erythematosus, idiopathic inflammatory myositis, and vasculitis (1)(2)(3)(4). Use of immunosuppressive agents and immune dysregulation are believed to play a pivotal role in the pathogenesis of the increased risk (5).…”
mentioning
confidence: 99%
“…Patients were eligible for the study if they were initially treated with GCs for a recently diagnosed (within 4 weeks prior to study entry) autoimmune disease using established criteria. 10 The cohort start date was defined as the time of initiation of the first GC prescription. The autoimmune diseases registered in this study were as follows: rheumatic diseases—systemic lupus erythematosus, mixed connective-tissue disease, polymyositis, dermatomyositis, vasculitis, Behçet disease, systemic scleroderma, adult-onset Still disease, Sjögren syndrome, rheumatoid arthritis, autoimmune bullous diseases, and anaphylactoid purpura; neurological diseases—multiple sclerosis, myasthenia gravis, and chronic inflammatory demyelinating polyneuropathy; gastrohepatobiliary diseases—ulcerative colitis, autoimmune hepatitis, autoimmune pancreatitis, and primary biliary cirrhosis.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we investigated the risk factors of symptomatic vertebral fracture, analyzing the database of cohort study conducted on patients with recently diagnosed autoimmune disease in the National Hospital Organization (NHO) hospitals between 2006 and 2008. 10 …”
Section: Introductionmentioning
confidence: 99%